The Antibacterial Effectiveness of Moringa Oleifera Leaves Extract Against the Growth of Escherichia coli Using the Diffusion Method - Liza Harum Nur Annisa; Linda Triana; Emilda Sari; Ari Nuswantoro (Borneo Scientific Publishing, 2024)
Moringa oleifera leaves a common herbal plant found in tropical regions and naturalized in Indonesia, are known to be rich in bioactive compounds such as flavonoids, tannins, terpenoids, alkaloids, and saponins. These compounds have potential medicinal properties, including antibacterial activity. This study aims to examine the antibacterial effectiveness of moringa leaf extract against the growth of Escherichia coli using the diffusion method. This descriptive-analytical research employed a purposive sampling technique with varying concentrations of moringa leaf extract: 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, and 100%. Each concentration was tested in triplicate, resulting in a total of 30 samples. The antibacterial effectiveness test was conducted using the agar diffusion method with blank paper disks. The results showed that no inhibition zones were formed at concentrations of 10% and 20%. Inhibition zones began to appear at 30% concentration (7.3 mm), increasing with higher concentrations: 40% (9 mm), 50% (10.3 mm), 60% (11.3 mm), 70% (16.6 mm), 80% (23.3 mm), 90% (28.3 mm), and reaching 34.6 mm at 100% concentration. Based on the antibacterial activity category, 10% and 20% showed no activity, 30% and 40% were categorized as weak, 50% and 60% as moderate, 70% as strong, and 80%, 90%, and 100% as very strong. It can be concluded that an 80% concentration of moringa leaf extract is the most effective in inhibiting the growth of Escherichia coli.